Set Up for Failure? Examining the Influence of Monetary Sanctions on Probation Success - Iratzoqui, Amaia (Criminal justice policy review, 2017)
Recent critiques of the decision to make monetary sanctions a condition of probation have suggested that the practice could hinder the successful completion of probation. However, few studies have explored this relationship empirically, and among those that do, the findings are relatively inconclusive and often dependent on the sample and measures used. Building on this research, the current study examines the imposition of four monetary sanctions on a sample of felony cases involving indigent adult probationers from a Florida public defender’s office. The results indicate that although monetary sanctions have relatively little impact on probation violations generally, the effects of these penalties vary based on the severity of the violation. Legal factors are consistently the most significant predictors of the likelihood and severity of probation violations.